Risk Management-Based Internal Audit for Auditor to Improve The Performance of Internal Audit Unit of PT Timah (Persero) Tbk - Bura, Esther; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2013)
PT. Timah (Persero) Tbk. is a holding company whose primary activity is related to tin mining operations and services marketing  products of their business group. During company's time course and development, PT.Timah (Persero) Tbk. Internal Audit Unit/SPI, as the internal audit executor, always face demands of dynamic personnel professionalism and working capacity in all conditions. Related to challenges in the process of task implementations and internal audit function, interrelation between risk management and internal audit was obtained. Therefore, it is unavoidable for internal audit activity to use risk management process. From a comparative study of  3 (three) domestic as well as foreign companies is PT Petrokimia Gresik, PT Sucofindo and Turk Tellekom (Turki), strong link was found between risk management and internal audit and their roles in improving internal audit of those companies.  Moreover, based on analysis results of PT.Timah (Persero) Tbk.'s role in carrying out its function and part, by using qualitatively-based research methodology, it was found that there were some weaknesses that could potentially reduce internal audit effectiveness and efficiency. Hence, a suitable approach of the application of risk management-based internal audit was proposed in form of a business solution for the internal audit unit of PT. Timah (Persero) Tbk. Benefits of the application was provided with reference to those 3 (three) domestic and foreign companies that have applied the approach. Keywords: Risk, Risk Management, Audit, Audit Internal